Optimization Design of Transmission System of Pulping Machine based on Genetic Algorithm - Chen Xianbing; Zhi Xuge; Song Haichao (Jixie chuandong)
The transmission system is a very important precision mechanism for twin- screw pulping machine equipment. However,that problem with characteristics of multi- objective function and multi constraints cannot be resolved in traditional optimization methods well,the optimization design is carried out based on genetic algorithm. Taking the volume of transmission system as the objective function,the optimization design is carried out. The results,which gives global optimal solution instead of locally optimal solution in traditional methods are much better. Finally,through the comparing of the simulation optimization results,by using the optimized new design scheme,the machine can meet various performance and constraints and be tighter and more reasonable.